Epidemiology of oral candidiasis: a household-based population survey in a medium-sized city in Amazonas (Research, Society and Development, 2021)
There was an increase in the number of elderly people in Brazil and, along with this fact, there was an increase in the incidence of oral candidiasis in this population, so the early identification of the disease and the etiologic agent for effective intervention is essential. The study aimed to describe the prevalence of oral candidiasis and its clinical manifestations, identifying Candida yeast species and their prevalence in the palatine mucosa and dentures in the palatine mucosa and dentures, comparing these factors in rural and urban elderly people in this city. The study was conducted in the city of Tefé, Amazonas, with elderly people aged 65 to 74 years old registered in primary health care services in urban and rural areas, where through sample calculation we had a total sample of 484 elderly people after losses and refusals. These elderly people were randomly selected from within the entire public service network, which enabled the samples to be collected in all municipal Basic Health Units. Data collection included clinical oral examinations (use, duration, and need for dental prosthesis) and collection of biological material with swabs, which were stored in CHROMAgar™ Candida medium, during home visits to determine the prevalence of the species through staining and colony morphology. Statistical analysis was performed with Stata MP software, using relative and absolute frequencies. The prevalence of oral candidiasis was found in 20.7% of the elderly in the different areas of residence studied. A greater number of cases and clinical manifestations of the disease were found in elderly people living in urban areas (p < 0.05). The odds ratios for developing the disease were higher in women, edentulous elderly, and users of dental prostheses. Candida albicans species were prevalent in infection and colonization of prostheses, while oral colonization showed similar percentages among Candida non-albicans (p = 0.657). As for the prevalence of species about the studied area of ​​residence, Candida albicans prevailed in the urban area and Candida non-albicans in the rural area (p